King and the dragonflies - Callender, Kacen (Thorndike Press large print striving reader collection., 2020)
Certain that his brother Khalid has transformed into a dragonfly after passing away, King often steals down to the bayou to search for him among the hundreds of dragonflies there. Khalid also visits King in his dreams, still, a secret King knows he has to keep--that, and the fact that he thinks he might be gay. Grief transforms King's family, but King learns how to use grief and pain to find beauty and redemption as his true self.